SUPERCOILED CIRCULAR DNA-PROTEIN COMPLEX IN Escherichia coli: PURIFICATION AND INDUCED CONVERSION TO AN OPEN CIRCULAR DNA FORM - Clewell, Don B. (1969)
The 23S twisted circular form of ColE(1) DNA has been isolated from Escherichia coli as a tightly associated DNA-protein complex with a sedimentation coefficient of approximately 24S. Treatment of this complex with pronase, trypsin, sodium dodecyl sulfate, Sarkosyl, or heat results in a conversion to a slower sedimenting form of 17S or 18S, as determined by centrifugation in neutral sucrose gradients. These treatments do not alter the sedimentation properties of noncomplexes supercoiled ColE(1) DNA even in the presence of the ColE(1)-protein complex. Electron microscopic analyses indicate that the decrease in sedimentation rate of the ColE(1)-protein complex after treatment with these various agents is largely owing to an induced transition of ColE(1) DNA from the supercoiled to the open circular state.